Africa's golden age debunked: a study of the sources of select black African historical novels - Ayivor, Moses Geoffrey Kwame (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1994)
The main thesis of this dissertation is that even a casual analysis of African writing reveals that contemporary African literature has and is still undergoing a distinctive metamorphosis. This change, which amounts to a significant departure from the early fifties, derives its creative impulse from demonic anger and cynical iconoclasm and is triggered by the mind-shattering disillusion that followed independence. The proclivity towards tyranny and the exploitation of the ruled in modern Africa is traced by radical African creative writers to an ancient source: the legendary and god-like rulers of precolonial Africa. Ouologuem's Bound to Violence and Armah's Two Thousand Seasons and The Healers hypothesize that past sins begot present sins. The legendary warrior heroes of the past, whose glory and splendour were once exalted in African writing, are now ruthlessly disentombed and paraded as miscreants and despots, who not only brutalized and sold their people into slavery but also ideologically fabricated their own legends and myths in order to maximize their tyrannical power. The preoccupation of these works is, therefore, to divest the ancient heroes of their false glory. contemporary critics tend to perceive this anti-traditional posture purely as a modern trend in African literature. The truth of the matter, however, is that the literary foundations of this anti-nativist/anti-Afrocentric literary tradition were laid by Thomas Mofolo and Sol Plaatje, whose Chaka (1925) and Mhudi (1930) are the precursors. The five primary works in this study parody and veer away from the generally accepted traditional African epic heroism and recorded history towards a communal heroic ideal which celebrates the larger community instead of the single epic heroes normally romanticized in African legendary tradition. These novelists, while dismantling the European and African myths about Africa's Golden Age, also disfigure the often glorified ancient historical landmarks and the fabled heroes of Africa's oral and recorded history. The rationale behind this investigation is the fact that though these works have innovated, assimilated, and parodied the African oral arts, particularly traditional African epic heroism, no detailed study has been made to explore the literary transformation these texts have undergone as written works. Treating African texts only as appendages of Western literature may undermine the ability of the critical evaluations which go into the heart of these texts and unravel their deeper meanings. The outcome of this kind of approach is that pertinent issues of style and theme originating from negro-African metaphysics, oral traditions, and iconography could thereby be left unexplored. Besides, the bulk of the current body of criticism on African literature, particularly on colonial Africa, tends to concentrate on colonialist Christian values and Western literary production models. One of the overriding concerns of this research, therefore, is to veer away from merely rehashing Eurocentric pronouncements on European influences and literary modes parodied by these works, by taking a fresh. look at the texts from the perspective of Afrocentrism and in particular from the point of view of the traditional African oral bards. To this end, therefore, the dissertation is divided into six main chapters and a short concluding chapter: Chapter 1, A Survey of Black Representations of Pre-colonial Africa, functions as an introduction, sketches the European image versus the Black counter-discourse, and locates the study within the current debate on the concept of pre-colonial Africa's Golden Age. Chapter 2, Thomas Mofolo's "Inverted Epic Hero", the nucleus of the study I analyzes the anti-epic and ironic modes manipulated by the text and also maps out the epic generic framework which structures the whole dissertation. Chapter 3, Traditional African Epic Heroism Revised, discusses Plaatje's Mhudi, paying special attention to the text's deployment of the African epic genre as well as the caricaturist and the anti-heroic modes. In Chapter 4, Yambo Ouologuem's Bound to Violence is examined under the title A World Trapped in an Orgy of Violence, Barbarism and Servitude. African oral art is used as the hermeneutic key in unlocking the complexities of Ouologuem's novel. Chapter 5, The African Anti-Legendary Creative Mythology, scrutinizes Armah's Two Thousand Seasons, highlighting, among other topics, Armah's daring innovative stylistic experimentation. Chapter 6, entitled The Akan Iconic Forest of Symbols, deals with Armah' s The Healers, concentrating on the Akan iconographic backdrop which shapes and informs this work. And finally, The Metamorphosis of Traditional African Epic Heroism, the title of the concluding chapter, sums up this dissertation.
Keywords: Mofolo, Thomas, 1875?-1948 -- Criticism and interpretation; Plaatje, Sol. T. (Solomon Tshekisho), 1876-1932; Armah, Ayi Kwei, 1939 -- Criticism and interpretation; Ouologuem, Yambo, 1940-; African literature -- 20th century -- History and criticism; African literature -- Black authors -- History and criticism